1983
DOI: 10.1002/abio.370030313
|View full text |Cite
|
Sign up to set email alerts
|

Regulation der fettsäurebildung bei der mikrobiellen alkanoxidation

Abstract: TibusstraBe 7 -15, D -4400 Miinster Biotechnologie-Symposium 1982, Leipzig, DDR SummaryAt the microbial oxidation of long-chain alkanes such monocarbonic acids a t a monoterminal oxidation are formed which correspond to the chain length of the alkanes. At diterminal oxidation the corresponding dioic acids are produced. Under the influence of cerulenin a direct incorporation of fatty acids into cell lipids increases. Undecanoic acid cannot be metabolized by Mwtierella isabellina. It causes an inhibition of alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As an alternative to monoterminal oxidation, ~0-oxidation may occur resulting in the pro-duction of either or both a,c0-dioic acids and c0hydroxy fatty acids. Rehm et al (1983) and Blasig et al (1988Blasig et al ( , 1989 have recently described the action of both mono-and diterminal oxidation systems in Mortierella isabellina and Candida spp., respectively. Woods & Murrell (1989) have reported that the propane-oxidising bacterium Rhodococcus rhodochrous can produce monoterminal and diterminal oxidation of C2-Cs n-alkanes via a system that is not linked to cytochrome P-450.…”
Section: Metabolism Of N-alkanesmentioning
confidence: 99%
“…As an alternative to monoterminal oxidation, ~0-oxidation may occur resulting in the pro-duction of either or both a,c0-dioic acids and c0hydroxy fatty acids. Rehm et al (1983) and Blasig et al (1988Blasig et al ( , 1989 have recently described the action of both mono-and diterminal oxidation systems in Mortierella isabellina and Candida spp., respectively. Woods & Murrell (1989) have reported that the propane-oxidising bacterium Rhodococcus rhodochrous can produce monoterminal and diterminal oxidation of C2-Cs n-alkanes via a system that is not linked to cytochrome P-450.…”
Section: Metabolism Of N-alkanesmentioning
confidence: 99%
“…Yeast CYP monooxygenase as well as CYP reductase are inducible by hydrocarbons and fatty acids but induction is also dependent on the growth phase, on the inner pH of the cell as well as on oxygen conditions [5,10,25,31,[39][40][41][42].…”
Section: Oxidation Mechanismsmentioning
confidence: 99%